14 - Book Review: Florence Etta and Sheila Parvyn-Wamahiu, 2003. Information munication Technologies for Development in Africa: The Experi Community Telecentres. Ottawa: CODESRIA and IDRC. Fore face, Acknowledgements, Executive Summary, Table, Figure ces,: DOI: 10.4314/ad.v30i1.22223 - Ngetich , Kibet A. (Africa Development, 2005)
Abstract